Pengembangan Potensi Desa Wisata dan Pengenalan Psikotropika di Desa Wirokerten, Kabupaten Bantul - Kurnianingtyas, Chandra Dewi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
This village potential development activity was carried out in Wirokerten Village, Bantul Regency. This service has two work programs, namely developing the potential of tourist villages and making pocket books. This service begins with identifying problems that exist in Wirokerten Village, then collecting data through sources on the internet, namely from regional websites, then planning programs and finally making outputs in the form of ebooks and videos. Before making the final report, all these activities are evaluated first. The result of the tourism village potential work program is the construction of the Bawal House. While the result of making a pocket book is the introduction of psychotropics and the consequences if they do abuse. Wirokerten Village has potential in the fisheries and tourism sectors which can then be developed into a tourist village with innovations in the form of design concepts for fish cultivation and fishing so that it is expected to increase community income, increase knowledge related to cultivation and increase the number of tourists. Counseling related to the introduction of psychotropics is expected to be able to provide insight and increase public knowledge about the types of psychotropics, how to recognize them and the dangers they pose.